factorize it correctly
Attachments:
![](https://hi-static.z-dn.net/files/d12/87b1007a6fdd72d6cd65a089994202db.jpg)
Answers
Answered by
0
x2 - x - 12 by spliting we get
x2-3x-4x-12
x(2-3)-4(2-3)
x2-3x-4x-12
x(2-3)-4(2-3)
Answered by
0
Hey mate
Here is your answer
---------------------------------------------
Product=(-12)=(4 x -6)
Sum=(-x)=(4+-3)x
=x^2+4x-6x-12
=x(x+4)-6x(x+4)
=(x+4)(x-6)
Hope it helps
Please mark as Brainliest
Here is your answer
---------------------------------------------
Product=(-12)=(4 x -6)
Sum=(-x)=(4+-3)x
=x^2+4x-6x-12
=x(x+4)-6x(x+4)
=(x+4)(x-6)
Hope it helps
Please mark as Brainliest
Similar questions